Product Innovation in the Global Fashion Industry (Palgrave Studies in Practice: Global Fashion Brand Management, 2018)
This volume explores the essence of the fashion evolution has been constant innovation, which is the utilization of new ideas to produce new products, processes, services or business practices. As an initial attempt to understand innovation in fashion, this volume focuses on product innovations, realizing that this industry is truly an innovative sector in which diverse technologies, science, art and tradition have been merged, synthesized and utilized to solve the needs and concerns of the end-users. In doing so, this book categorizes product innovation into three levels-materials, style and product development-and aims to present the broader scope of innovation in the global fashion industry with the hope that other sectors can learn from these developments and be inspired. This volume consists of five chapters combining theory with practice, through the analysis of 4 case studies: Stone Island (menswear - Italy), Geox (shoes and apparel - Italy), Nike (sportswear - USA) and Repetto (dance-inspired products - France). .